(untitled) (Lex Journal : Kajian Hukum dan Keadilan, 2025)
This research aims to analyze the legal consequences of the inclusion of standard clauses containing exoneration clauses in agreements based on the Civil Code, analyze consumer protection against the inclusion of standard clauses containing exoneration clauses in parking agreements based on the GCPL and analyze the responsibility of parking managers for the loss of consumer vehicles in the parking area based on the GCPL. The type of research used in this research is normative legal research using a statute approach, a conceptual approach, and a case approach. The legal consequences of including standard clauses containing exoneration clauses in agreements based on the Civil Code are null and void. In consumer protection against the inclusion of standard clauses containing exoneration clauses in parking agreements, there are two types of legal protection efforts: preventive and repressive. Preventive legal efforts in the scope of consumer protection against the inclusion of standard clauses containing exoneration clauses in parking agreements are Article 18, paragraph (1), letter (a), prohibiting business actors from including standard clauses in every agreement and document that states the transfer of responsibility. While repressive legal remedies aim to resolve problems that arise, consumers can claim compensation and choose to resolve disputes through or out of court. Regarding the responsibility of parking managers for the loss of consumer vehicles in the parking area, it is regulated in Article 19, paragraph (2) of Law Number 8 of 1999 concerning Consumer Protection.